Prevalence and factors associated with urogenital schistosomiasis among primary school children in barrage, Magba sub-division of Cameroon - Anna Longdoh Njunda; Emmanuel Ngala Ndzi; Jules Clement Nguedia Assob; Henri-Lucien Fawmno Kamga; Emmanuel Tebit Kwenti (BMC, 2017)
Abstract Background The purpose of this study was to determine the prevalence and intensity as well as the factors associated with urogenital schistosomiasis (US) in Barrage, a rural community around the Mape΄ dam, in the West region of Cameroon not previously documented for transmission. Methods In this cross sectional parasitological survey, 382 children were enrolled from three primary schools in the study area between March and May 2016. A semi-structured questionnaire was used to collect information on demographics, clinical and predisposing factors. The syringe filtration technique was used to analyse urine samples. Samples with visible or gross haematuria were recorded prior to filtration. The Pearson chi-square, the student T-test and logistic regression were all performed as part of the statistical analyses. Results The overall prevalence of US was 41.1% (95% CI: 36.1-46.2). Infection was more common in children below 10 years (p = 0.009), in males (p = 0.029), and in children who frequently come into contact with water from the dam (p < 0.001). Furthermore, US was more common in children attending Ecole Public (EP) Manbonko Bord (81.1%, p < 0.001) which is very close to the dam and in children from a fishing background (80.9%, p < 0.001). On the contrary, knowledge about schistosomiasis was not observed to be associated with prevalence. In this study, the intensity of infection was observed to be higher in children below 10 years (p < 0.001), in males (p = 0.001), and in children attending EP Manbonko Bord (p < 0.001). The intensity of infection was also highest in children presenting with haematuria (p < 0.001). Frequent contact with water from the dam and having parents whose occupation was fishing were identified as the associated factors for US. Conclusion A high prevalence of US was observed in school-aged children in the study area especially in those attending EP Manbonko Bord. Limiting contact with water from the dam, control of the snail intermediate host, provision of portable water and mass treatment of the entire population are proposed as some of the measures to reduce and eventually eliminate transmission in the area.